Design of Accounting Learning Model Through the Positive Divergent Stimulation Under Mental Accounting Dilemma - Satia Nur Maharani; Setya Ayu Rahmawati (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
The nature of scientific accounting significantly influences cognitive processes in individuals studying the discipline. This study examines how cognitive mental processes, specifically mental accounting, shape one's ability to approach accounting concepts with innovation. Within accounting education, the Creative Problem Solving (CPS) technique, known for stimulating divergent thinking, is explored as a means to enhance cognitive creativity. This model provides learners with tools to tackle challenges, generate new ideas, and navigate transformative changes. The research emphasizes the crucial role of mental accounting in achieving success in divergent thinking in the context of accounting. Mental accounting can manifest both positively and negatively, influenced by various learning approaches. Our investigation focuses on how accounting students can cultivate positive divergent thinking amidst cognitive mental accounting dilemmas, informed by an extensive literature review. The study concludes with the development of a model that highlights the cultivation of positive divergent thinking within cognitive mental accounting challenges.